2015
DOI: 10.1038/nature14685
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the eukaryotic MCM complex at 3.8 Å

Abstract: DNA replication in eukaryotes is strictly regulated by several mechanisms. A central step in this replication is the assembly of the heterohexameric minichromosome maintenance (MCM2-7) helicase complex at replication origins during G1 phase as an inactive double hexamer. Here, using cryo-electron microscopy, we report a near-atomic structure of the MCM2-7 double hexamer purified from yeast G1 chromatin. Our structure shows that two single hexamers, arranged in a tilted and twisted fashion through interdigitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
279
4
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(305 citation statements)
references
References 72 publications
21
279
4
1
Order By: Relevance
“…For example, studies on the CMG helicase and its subcomplexes have established that the MCM is a six-member ring with an N-terminal domain that serves as a processivity collar (15) and a C-terminal ATPase motor domain that provides the DNA unwinding function (16)(17)(18)(19)(20)(21). High-resolution cryo-EM analysis has shown that the ATPase motor translocates on the leading-strand template (22), in agreement with work on Xenopus embryo extracts (23).…”
mentioning
confidence: 50%
“…For example, studies on the CMG helicase and its subcomplexes have established that the MCM is a six-member ring with an N-terminal domain that serves as a processivity collar (15) and a C-terminal ATPase motor domain that provides the DNA unwinding function (16)(17)(18)(19)(20)(21). High-resolution cryo-EM analysis has shown that the ATPase motor translocates on the leading-strand template (22), in agreement with work on Xenopus embryo extracts (23).…”
mentioning
confidence: 50%
“…Three of the complexes, representing prominent stages of DNA replication, have been structurally characterized recently by cryo-EM at high resolution: the OCCM, the MCM2-7 DH, and the CMG ( Fig. 4A-C; Costa et al 2011Costa et al , 2014Sun et al 2013Sun et al , 2014Li et al 2015;Yuan et al 2016Yuan et al , 2017Georgescu et al 2017). Interestingly, the Mcm subunit conformations are different in these three complexes, reflecting distinct functional states.…”
Section: Mcm2-7 Conformations In the Occm Dh And Cmg Reveal Mcm2-7 mentioning
confidence: 99%
“…In contrast, activated CMG complexes at replication forks contain a single Mcm2-7 complex and encircle ssDNA (Fu et al 2011;Yardimci et al 2012;Sun et al 2015;Georgescu et al 2017). Structural studies have captured Mcm2-7 at multiple stages during helicase loading and in the CMG complex (Sun et al 2013;Li et al 2015;Abid Ali et al 2016;Yuan et al 2016;Georgescu et al 2017). These structures have provided important insights into Mcm2-7 loading and the interactions of Mcm2-7 with Cdc45 and GINS.…”
mentioning
confidence: 99%